Coping with Disease-Related Deficiency in Patients with Various Degrees of Life-World Stability - I. O. Loginova; E. A. Kudashova (СибСкрипт)
Disease provokes vulnerability, affects lifestyle, and reduces social interaction. In chronic patients, deficiency manifests itself as a lack of inner resources. Although deficiency and compulsion are common phenomena, publications on coping strategies remain understudied when it comes to somatic diseases. This research featured life and coping strategies in patients with imposed deficiency and different degrees of life-world stability. The study involved 420 patients with somatic diseases associated with major lifestyle changes. It included I. O. Loginova’s Questionnaire of Life Scenario and the Technique of Life-World Stability. The coping strategies identified by clinical and psychological interview proved to correlate with the degree of life-world stability. The patients with low life-world stability were prone to informing, self-suggestion, self-control, food treats, walking, and rituals. Those with a medium degree of life-world stability preferred informing, self-motivation, self-control, avoiding comparisons, new activities, hobbies, walking, and physical activity. The patients with strong life-world stability chose informing, involvement, self-motivation, positive thinking, avoiding comparisons, hobbies, walking, and cultural entertainment.